Integration laboratories-sanitary surveillance: a review - Lopes, Rosane Gomes Alves (2017)
This integrative review with systematic search aimed to identify national and international literature on laboratory and sanitary surveillance to reflect on the integration of these services in the National System of Sanitary Surveillance Three repositories were used: Banco de Teses e Dissertações; Scientific Electronic Library Online - Brazil and Pubmed Central. The selection followed pre-defined criteria and the analysis considered: type of academic production (masters, doctorate or scientific article), year and institution of origin, and theme focused. Master’s degree theses (64.7%) from the Oswaldo Cruz Foundation (36.5%) were predominant, from which 90% were elaborated at the Foundation’s National Institute for Quality Control in Health. The quality control of products is an important area of publications (41, 5%), including food, medicines and vaccines. Studies related to public policies and health surveillance included: generic drugs; pharmaceutical equivalence studies; food and nutrition; and integration of the National Sanitary Surveillance Agency with other actors in vaccine innovation and in the Brazilian Network of Analytical Laboratories in Health. Integration was expressed through cooperative activities between laboratories and services, and it remains to be improved in view of the fact that, in Brazil, the laboratories and the surveillance services are differentiated and are linked to different governmental entities.